2012
DOI: 10.2478/v10058-012-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Regional Peculiarities of Strongylid (Nematoda, Strongylidae) Biodiversity in Domestic Horses in Ukraine

Abstract: Analysis of Regional Peculiarities of Strongylid (Nematoda, Strongylidae) Biodiversity in DomesticHorses in Ukraine. Kuzmina T. A. -Analysis of regional peculiarities of species composition and structure of strongylid communities in domestic horses from various parts of Ukraine is presented. More than 86,000 strongylid specimens were collected using the diagnostic deworming technique from 180 horses in 10 regions (Kyivska, Kyrovogradska, Poltavska, Kharkivska, Sumska, Donetska, Ternopilska, Zakarpatska, Kherso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Signifi cant differences with infection of intestinal parasites associated with age were observed only for Strongylidae, P. equorum and O. equi (Table 3). Our data are consistent with similar observations on brood domestic horses (Hoglund et al, 1997;Lind et al, 1999;Larsen et al, 2002;Kornas et al, 2010;Kuzmina, 2012), and support the concept on the development of anti-parasite immunity in horses with age (Klei & Chapman, 1999). Concerning H. muscae, A. perfoliata and G. intestinalis, signifi cant differences in the levels of infection of horses of different ages were not detected.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Signifi cant differences with infection of intestinal parasites associated with age were observed only for Strongylidae, P. equorum and O. equi (Table 3). Our data are consistent with similar observations on brood domestic horses (Hoglund et al, 1997;Lind et al, 1999;Larsen et al, 2002;Kornas et al, 2010;Kuzmina, 2012), and support the concept on the development of anti-parasite immunity in horses with age (Klei & Chapman, 1999). Concerning H. muscae, A. perfoliata and G. intestinalis, signifi cant differences in the levels of infection of horses of different ages were not detected.…”
Section: Discussionsupporting
confidence: 92%
“…In the analysis of species composition of the strongylid communities we found that ST horses harbored the lowest number of species of these nematodes (15), while the highest species biodiversity (30 or 31) was documented in FR horses. Our fi ndings correspond to the results of other authors who conducted similar studies in Poland (Kornas et al, 2006;Pilarczyk et al, 2010), as well as in other countries (Hoglund et al, 1997;Lind et al, 1999;Larsen et al, 2002;Kuzmina et al, 2007Kuzmina et al, , 2009Kuzmina et al, , 2011Kuzmina, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By necessity, horses enrolled in NAm anthelmintic efficacy critical tests and in EEur diagnostic deworming studies generally had no or limited anthelmintic exposure immediately prior to enrollment and were prescreened for patent infections based on positive fecal egg counts [27][28][29][30][31][32][33][34], often meeting a predetermined threshold of 200 eggs per gram of feces (EPG) [35,36]. In fact, all EEur diagnostic deworming horses from the 18 (of 19 total) datasets, for which pretreatment egg counts were reported, regardless of enrollment criteria, exhibited pretreatment fecal egg counts > 200 EPG [8,[31][32][33][35][36][37]. Thus, cyathostomin prevalence in these horses was 100%, and, although there is no linear correlation of strongyle-type EPG with adult worm burden [38], enrolled horses had patent infections less likely to be negligible than horses with egg counts that were negative or below the threshold.…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that constraint of horse enrollment to female horses one year of age or older with detectable, patent cyathostomin infections resulted in consistent prevalence overestimation by NAm critical tests and EEur diagnostic deworming in relation to respective regional standard necropsies. By necessity, horses enrolled in NAm anthelmintic efficacy critical tests and in EEur diagnostic deworming studies generally had no or limited anthelmintic exposure immediately prior to enrollment and were prescreened for patent infections based on positive fecal egg counts [ 27 – 34 ], often meeting a predetermined threshold of 200 eggs per gram of feces (EPG) [ 35 , 36 ]. In fact, all EEur diagnostic deworming horses from the 18 (of 19 total) datasets, for which pretreatment egg counts were reported, regardless of enrollment criteria, exhibited pretreatment fecal egg counts > 200 EPG [ 8 , 31 33 , 35 37 ].…”
Section: Discussionmentioning
confidence: 99%